Water and Wastewater Treatment (IntechOpen, 2023)
The use of water, one of the most valuable and vital resources in the world, should respond to growing needs, and used water should not have negative effects on the environment. Research on the reduction of used water and wastewater quantities, post-use treatment, or reuse/recovery methods is increasing day by day. These studies focus on finding the most appropriate method from both technical and economic perspectives. In this book, emerging technologies and materials used in the treatment, reuse, or recovery of various kinds of water and wastewaters are examined. The book consists of valuable scientific research specifically including desalination and use of renewable energy, nanomaterials, biosorbents, photocatalytic treatment, as well as riverbank filtration and wetlands. The editor would like to record his sincere thanks to the authors for their contributions.